Perbaikan Aliran Proses Operasi Layanan untuk Mengurangi Pemborosan dengan Pendekatan Lean Service (Studi Kasus: Klinik Citra Medika Medan Marelan) - Abdul Azis Syarif (Universitas Teuku Umar, 2020)
Klinik Citra Medika Medan Marelan is one of the service companies in the field of health services. The problems that occur in the service process are the number of non-value added activities that affect the service process flow. Improvements were made to solve the problem by applying the lean service concept to service. In the application of lean service used VSM (Value Stream Mapping) as a method to explain the flow of processes in visual form. The results of identification with VSM namely process activity mapping obtained 25.15% value added activity, 48.99% non value added activity, and 25.86% is necessary but not value added activity. The results of waste identification in the questionnaire obtained waste that often occurs in the service process, namely the process of getting approvals with a weight of 139, bocklog in work qeeves with weight 137, waiting for the next step with a weight of 136.5, doing unnecessary work not requested with a weight of 134, 5, transport of document with a weight of 131.5 and an error in document with a weight of 129.5.